The CHL Class Action Settlement – Is the Tail Wagging the Dog? - Thornicroft, Kenneth Wm. (2024)
Discusses the CHL class actions and the settlement in Ontario and Alberta as well as the failure to settle in Quebec. Concludes that the present state of affairs is very unsatisfactory.

Health and Safety: Amazon Fails to Deliver - Gindin, Sam (Amazon Worker Solidarity, 2024)
Discusses injury rates of warehouse workers at Amazon, with particular reference to Ontario. Concludes that workers must organize to counterbalance the management priorities of the world's second largest corporation.

Ontario Court Approves $30 Million Class-Action Settlement Over Employment Status of Canadian Hockey League Players in OHL, WHL and QMJHL - HR Law Canada (2024)
The Ontario Superior Court of Justice has approved a $30 million settlement resolving class action lawsuits regarding the employment status of players in the Canadian Hockey League’s Ontario Hockey League (OHL), Western Hockey League (WHL), and Québec Major Junior Hockey League (QMJHL). The decision comes after a complex legal battle spanning nearly a decade, affecting approximately 4,286 amateur hockey players. But it still needs to be approved by courts in Alberta and Quebec.

Temporary Foreign Workers Maritimes - Cooper Institute; Dalhousie University; St. Thomas University; United Food and Commercial Workers Canada; Madhu Verma Migrant Justice Centre (2024)
Migrant Workers in the Canadian Maritimes is a research and knowledge dissemination platform coordinated between Dalhousie University (Halifax, Nova Scotia), St. Thomas University (Fredericton, New Brunswick) and Cooper Institute (Charlottetown, Prince Edward Island). It involves the establishment of a collaboration amongst community allies: The Filipino-Canadian CommUNITY of New Brunswick (FCNB); KAIROS: Canadian Ecumenical Justice Initiatives (New Brunswick); United Food and Commercial Workers Union (UFCW); Madhu Verma Migrant Justice Centre; and intends to examine the health and safety of temporary foreign workers (TFWs). –Website description
https://www.cbc.ca/listen/live-radio/1-27/clip/16104380